Responsible Innovation Business Opportunities and Strategies for Implementation - Jarmai, Katharina (SpringerBriefs in Research and Innovation Governance, 2020)
This Open Access book, Responsible innovation provides benefits for society, for instance more sustainable products, more engagement with consumers and less anxiety about emerging technologies. As a governance tool it is mostly driven by research funders, including the European Commission, under the term "responsible research and innovation" (RRI). To achieve uptake in private industry is a challenge. This book provides successful case studies for the implementation of responsible innovation in businesses. The importance of social innovations is emphasized as a link between benefits for society and profits for businesses, especially SMEs. For corporate industry it is shown how responsible innovation can offer a competitive advantage to adopters. The book is based on the latest insights from theory and practice and combines conceptual work with first-hand experience. It is of interest to innovation managers, entrepreneurs and academics. For academics, the book will provide a combination of analysis and discussion, and present recent learnings from first-hand interaction with entrepreneurs. For innovation managers and entrepreneurs, it will provide inspiration and better ideas about what responsible innovation can look like in practice, why others have "done it" and what the potential benefits might be. The book will thus serve the purposes of spreading the word about the responsible innovation concept among different audiences whilst making it more accessible to innovation managers and entrepreneurs.